Antimicrobial activity of ocimum gratissimum extract on Suya (an intermediate moisture meat) in Nigeria (2009)
Extract of Ocimum gratissimum leaves war used oh Suya meat (an intermediate moisture meat) harvested at different hours of soaking period. O. gratissimum leaves were collected from Oyo state, South West region of Nigeria, rinsed in distilled water and squeezed la extract the fluid. The meat used was semimembranous muscle from beef carcass which was trimmed of all visible fat and connective tissues. The meat cut was sliced to sheets of 0.18cm-0.35cm thick and lengths of between 5.0cm-7.1cm. The study comprised of five treatments of 10 replicates each. Treatment A (TA) served as the control- (Suya without Ocimum Gratissimum Extract-OGE), while (TB),(TC),(TD) and (TE) were soaked in OGE for 1/2 hr, 1hr, 1 1/2hrs and 2 hrs respectively, before coating with Suya ingredients. A total of 50 sticks of Suya with an average weight of 38.10 - 59.30grams of sliced meat per stick were prepared for each treatment sample. The meats on sticks were properly coated with Suya ingredient. The morphological and biochemical characterization of aerobic bacteria, coliform and lactic acid isolates from the five treatments was carried out. At Day 0: From samples of the five treatments were isolated, five (5) Aerobic species (namely: Pseudomonas sp Bacillus sp, Micrococcus sp and Flavobacterium sp. Three (3) Coliforms sp were also isolated namely: Proteus sp, Aeromonas sp and Enterobacter sp. Four (4) Lactic acid bacteria were also isolated namely: Pediococcus sp Streptococcus sp, Lactobacillus sp and Enterococcus feacalis. Suya meat soaked in OGE at different harvesting hours 1/2hr, lhr, 1 1/2hrs and 2hrs, on the days ranged between 0.01 x10(5) to 0.07 x 10(5); 1.0 x 10(5) to 0.04 x 10(5); 0.1 x 10(5) to 3.0 x 10(5) and 0.01 x 10(5) to 0.2 x 10(5) respectively however, the microbial counts were relatively low at third and fifth days which might be as a result of the active chemotypes in OGE. Coliform counts for Day 7 for TA and TB were exceptionally high.